Slovensko gozdarstvo pred izzivi 21. stoletja - Diaci, Jurij (Gozdarski vestnik, 2009)
The goal of this article is to compare Slovenian forests and forestry with theworld and European trends and policies and to point out the developmental challenges for the Slovenian forestry that should be taken into account while implementing the National Forest Program. The development of the forests and forestry in the developed and developing world differ, but the global ecological problems are common; the priority tasks for ending the unfavorable environment changes while the needs for ecosystem services are increasing, aretherefore uniform. Fast changes of the natural and social environment will mark forest management in the future; the main challenges for Slovenian forestry we can expect in the 21st century are: 1) a more active forest management and increased wood use; 2) ensuring forest health and stability in conditions of climatic changes; 3) sustaining forest biodiversity while increasing their use; 4) improving the competitiveness of the forestry sector from the viewpoint of the economy and working conditions; 5) developing, evaluating and marketing the non-timber forest goods. The operational program for performing the national forest program should be based on a broad consent for achieving the goals in the National Forest Program. The past results and comparison with forestry policies of the developed countries show that more directional instruments from the state are needed, since the market did not adequately regulate the conditions in forests and forestry in the past period.
Keywords: forestry; gozdarstvo; razvoj; gozdarska politka; nacionalni programi; Europe; Evropa